Jewish women in the medieval world - Ifft Decker, Sarah, author.
1 online resource.
Keywords: "Jewish Women in the Medieval World offers a thematic overview of the lived experiences of Jewish women in both Europe and the Middle East from 500 to 1500 CE, a group often ignored in general surveys on both medieval Jewish life and medieval women. With the inclusion of a Chronology, Who's Who, Documents section, and Glossary, this study is an essential resource for students and other readers interested in both Jewish history and women's history"--